(untitled) (UUM Journal of Legal Studies, 2013)
The aim of this paper is to create awareness of the threats of online gaming to Malaysia and the International society in various areas such the involvement of money laundering via online gaming. It also includes suggestions of countermeasures and regulations that could be implemented in Malaysia. The paper will achieve this by having an insight of the accessibility of the online gambling to Malaysians and the law and regulations available in Malaysia to combat and cater the existence of online gambling. Law regulating gambling in general could be found in Betting Ordinance 1953 and Common Gaming House Act 1953. Account of initiatives taken to be taken by the Malaysian government will be in scrutiny in this paper. In addition, a review into the other jurisdictions from United Kingdom, United States and the available international law and regulations on online gambling such as the European Commission Green Paper: Online Gambling in the Internal 2011. Besides, the paper will also be viewing into the legislations of Commonwealth countries such as Australia on the online gaming such as the Interactive Gaming Act 2001. Nevertheless, there will be an in-depth view relationship of money laundering and online gambling. There will be suggestions of possible mechanism to regulate the online gambling activities in Malaysia in order to protect the interest of the people. Malaysia has legislations on gambling which do not specifically touches on online gambling and probably could be revised with new provisions in regulating the new entity, the online gambling. The practical implication of this paper is to emphasise the utmost importance of having awareness and revised strategies against the threat of online gambling which involved the unlimited access of internet and the inevitable necessities of new legislations and control mechanisms by the government authority to curb the peril. This paper could provide